2014
DOI: 10.1097/opx.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Provider Use of Collaborative Goal Setting with Glaucoma Patients

Abstract: Purpose The purpose of this preliminary study was to describe the extent to which providers used collaborative goal setting and individualized assessment with patients who were newly prescribed glaucoma medications. Methods English-speaking glaucoma suspect patients from six ophthalmology clinics who were newly prescribed glaucoma medications had their medical visits video-tape recorded and were interviewed after the visits. The video-tapes were transcribed and coded to examine provider use of collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“… 50 However, such findings stand in contrast with glaucoma research indicating that patients' views and treatment goals may not be adequately explored. 51 Our results highlight the need for providers to remain vigilant for sociobehavioral determinants, particularly because less observable factors such as acute psychological stress have been associated with elevated IOP. 52 …”
Section: Discussionmentioning
confidence: 67%
“… 50 However, such findings stand in contrast with glaucoma research indicating that patients' views and treatment goals may not be adequately explored. 51 Our results highlight the need for providers to remain vigilant for sociobehavioral determinants, particularly because less observable factors such as acute psychological stress have been associated with elevated IOP. 52 …”
Section: Discussionmentioning
confidence: 67%
“…13 Clinical clinician-patient communication. 9,[23][24][25] In one report they examined whether specific aspects of clinicianpatient interaction were associated with treatment adherence in the 60 days after the consultation. They found that provider information on how to instil drops was associated with improved adherence, but this information was only given in 14% of visits.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-one of the patients in Sleath et al's cohort were commenced on glaucoma treatment for the first time during the videotaped consultations and they concluded that clinicians did not use collaborative goal setting or take into account the individuals' views on glaucoma and its treatment. 9 In only 19 of the 51 (37%) were patients given a treatment choice, and 13 of this 19 involved one clinician. Furthermore, of the 15 physicians who started patients on glaucoma treatment during this study, only 5 (33%) gave treatment choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations